NAVIGATING THE EVOLUTION OF EDUCATION: IN-DEPTH EXPLORATION OF EMERGING PEDAGOGICAL STRATEGIES AMID GLOBAL CHANGESWITH A FOCUS ON ENGLISH LANGUAGE TEACHING - Husna Imro'athush Sholihah; Eliagus Telaumbanua; Martha Surya Dinata Mendrofa; Yuda Septian Kurniawan; Muhammad Ishom (Adisam Publisher, 2024)
This comprehensive exploration delves into the evolving landscape of education, particularly emphasizing emerging pedagogical strategies. As the global educational paradigm undergoes transformative changes, this study navigates through the intricacies of these shifts, focusing on English Language Teaching (ELT) as a critical component. The examination encompasses historical foundations, current methodologies, and future trajectories, providing a nuanced understanding of the interplay between pedagogical strategies and global educational dynamics. The analysis considers the role of technology, socio-economic influences, and issues of accessibility and inclusivity within the context of ELT. By synthesizing insights from diverse sources, this study aims to contribute to the ongoing discourse on educational evolution, providing valuable perspectives for educators, researchers, and policymakers.